2020
DOI: 10.1152/ajpheart.00469.2019
|View full text |Cite
|
Sign up to set email alerts
|

Maternal microbiome and the hypertensive disorder of pregnancy, preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy-specific disorder that can be life threatening for both mother and baby. It is characterized by a new onset hypertension during the second half of pregnancy and affects ~300,000 women in the United States every year. There is no cure for PE, and the only effective treatment is delivery of the placenta and the fetus, which is often preterm. PE is believed to be a severe manifestation of placental dysfunction due to early angiogenic imbalances and inflammatory disturbances; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 97 publications
0
30
0
4
Order By: Relevance
“…The levels of BP, urine protein and fetal death were increased, whereas fetal body weight was decreased in the L-NAME group in the present study. hypertension is one of the pathophysiological factors resulting in PE and injuries of the systematic inflammatory response (22). E2 improved the biochemical indexes and neonatal outcome by reducing BP, urine protein and the rate of stillbirths, increasing fetal weight and attenuating pathological injury, which indicated that the improvement of PE was associated with E2 treatment.…”
Section: Discussionmentioning
confidence: 95%
“…The levels of BP, urine protein and fetal death were increased, whereas fetal body weight was decreased in the L-NAME group in the present study. hypertension is one of the pathophysiological factors resulting in PE and injuries of the systematic inflammatory response (22). E2 improved the biochemical indexes and neonatal outcome by reducing BP, urine protein and the rate of stillbirths, increasing fetal weight and attenuating pathological injury, which indicated that the improvement of PE was associated with E2 treatment.…”
Section: Discussionmentioning
confidence: 95%
“…The cytotrophoblast fails to remodel spiral arteries, leading to hypoperfusion and ischemia of the placenta that provoke generalized maternal endothelial dysfunction and consequently the clinical manifestations of disease. Until now, placenta and fetus delivery has been the only effective treatment ( Martinez-Fierro et al, 2018a ; Beckers and Sones, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 PE is a placental disorder leading to high maternal and fetal morbidity and mortality. 3,4 However, due to the lack of early prediction and targeted therapy, termination of pregnancy has become the most effective treatment. 5 Mechanistically, abnormal trophoblast function and uterine spiral artery remodeling disorders are recognized as the pathophysiological basis of PE.…”
Section: Introductionmentioning
confidence: 99%